The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1242/jeb.218776
|View full text |Cite
|
Sign up to set email alerts
|

The influence of training-induced sarcomerogenesis on the history dependence of force

Abstract: The increase or decrease in isometric force following active muscle lengthening or shortening, relative to a reference isometric contraction at the same muscle length and level of activation, are referred to as residual force enhancement (rFE) and residual force depression (rFD), respectively. The purpose of these experiments was to investigate the trainability of rFE and rFD on the basis of serial sarcomere number (SSN) alterations to history-dependent force properties. Maximal rFE/rFD measures from the soleu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 87 publications
11
28
1
Order By: Relevance
“…Hence, the fascicle length adaptations we observed did not appear to impact voluntary rFE. This agrees with the findings of Power et al, 46 in which agerelated decreases in fascicle length did not contribute to differences in rFE, and Chen et al, 43 in which changes to serial sarcomere number did not impact absolute and relative rFE. Chen and Power, 17 however, saw an 89% increase in relative rFE following concentric training and a 36% decrease following eccentric training that corresponded to changes in fascicle length.…”
Section: Influence Of Training On Rfesupporting
confidence: 92%
See 3 more Smart Citations
“…Hence, the fascicle length adaptations we observed did not appear to impact voluntary rFE. This agrees with the findings of Power et al, 46 in which agerelated decreases in fascicle length did not contribute to differences in rFE, and Chen et al, 43 in which changes to serial sarcomere number did not impact absolute and relative rFE. Chen and Power, 17 however, saw an 89% increase in relative rFE following concentric training and a 36% decrease following eccentric training that corresponded to changes in fascicle length.…”
Section: Influence Of Training On Rfesupporting
confidence: 92%
“…Fascicle length changed as expected following short-and long-MTU training ( Figure 4) and those changes did not relate to changes in relative rFD ( Figure 5A), therefore, the passive fascicle length adaptations we observed did not appear to impact voluntary rFD. These results echo those found by Chen and Power,17 in which relative rFD did not change following concentric or eccentric training, as well as those from Chen et al, 43 in which serial sarcomere number changes in rats following uphill and downhill running training did not alter absolute and relative rFD in vitro.…”
Section: Influence Of Training On Rfdsupporting
confidence: 90%
See 2 more Smart Citations
“…Similarly to Blazevich et al (2003), our results show increases in VL Lf following PLT; this phenomenon is expected to reflect an increase in the number of sarcomeres in series, and thus in maximum shortening velocity (Bodine et al, 1982). Animal studies have shown that sarcomere addition can occur already after 5, 10, and 28 days in response to training modalities involving muscle lengthening (Lynn et al, 1998;Butterfield et al, 2005;Chen et al, 2020). However, recent studies in intact whole mice muscle have described some variability in sarcomere length along different muscle regions (Moo et al, 2016), which become even more non-uniform upon activation (Moo et al, 2017).…”
Section: Adaptations In Muscle Architecturesupporting
confidence: 61%